Homogeneous Catalysis in N-Formylation/N-Methylation Utilizing Carbon Dioxide as the C1 Source - Dutta, Indranil; Gholap, Sandeep Suryabhan; Rahman, Mohammad Misbahur; Tan, Davin; Zhang, Lili; Dighe, Shashikant U; Huang, Kuo-Wei (Chemistry, an Asian journal, 2024)
The growing emphasis on sustainable chemistry has driven research into utilizing carbon dioxide (CO ) as a nontoxic, abundant, and cost-effective C1 building block. CO offers a promising avenue for direct conversion into valuable chemicals ranging from fuels to pharmaceuticals. This review focuses on the utilization of CO for reductive N-formylation/N-methylation reactions of various amines, providing advantages over conventional methods involving toxic CO and other methylating reagents. The approach employs readily available reductants such as silane, borane reagents, and hydrogen (H ) The discussion encompasses recent developments in transition metal and organocatalyst systems for these reactions, highlighting mechanistic interpretations and factors influencing product selectivity.